Method for manufacturing laminate

By performing two spin coating operations on the surface of the substrate, the metal nanowires are distributed radially using different rotation centers, the problem of difficult to reduce resistance in the prior art is solved, and a laminate with low resistance value and excellent light transmittance is realized manufacture.

CN119156260APending Publication Date: 2024-12-17NIKON ESSILOR
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380040729.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-24
Filing Date
2023-05-12
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The prior art is difficult to manufacture a laminated body with a low resistance value without reducing light transmittance, especially in a transparent conductive film containing metal nanowires, and the resistance value is difficult to effectively reduce.

Method used

By performing two spin coatings on the surface of the substrate, the first spin coating of a composition containing metal nanowires and solvents is spin coating. During the second spin coating, the metal nanowires are radially distributed based on different rotation centers, thereby increasing the number of times the spin coating. Crossing point, lowering the resistance value.

Benefits of technology

It is achieved that the resistance value of the laminated body is significantly reduced without reducing the light transmittance, and the conductivity and anti-static properties are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119156260A_ABST
    Figure CN119156260A_ABST
Patent Text Reader

Abstract

The present invention addresses the problem of providing a method for producing a laminate that exhibits a low resistance value and excellent light transmittance. This method for producing a laminate comprises: a first step in which a substrate is rotated and a composition containing metal nanowires and a solvent is spin-coated on the surface of the substrate; and a second step in which the substrate obtained in the first step is rotated, and a composition containing metal nanowires and a solvent is spin-coated on the surface of the substrate on which the composition is spin-coated in the first step. The position of the center of rotation of the base material in the first step is different from the position of the center of rotation of the base material in the second step. The obtained laminate includes the substrate and a metal nanowire layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a method for producing a laminate. Background Art

[0002] Patent Document 1 discloses a transparent conductive film containing metal nanowires, and discloses that a coating liquid containing metal nanowires is applied to a substrate to form the transparent conductive film containing metal nanowires.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2012-216535 Summary of the invention

[0006] The present disclosure relates to a method for manufacturing a laminate, wherein the laminate comprises a substrate and a metal nanowire layer, and the method for manufacturing the laminate comprises the following steps: a first step of rotating the substrate and spin-coating a composition comprising metal nanowires and a solvent on the surface of the substrate; and a second step of rotating the substrate obtained in the first step and spin-coating the composition comprising metal nanowires and a solvent on the surface of the substrate on which the composition is spin-coated in the first step, wherein the position of the rotation center of the substrate in the first step is different from the position of the rotation center of the substrate in the second step. BRIEF DESCRIPTION OF THE DRAWINGS

[0007] Figure 1 This is a diagram for explaining an example of an embodiment of a method for producing a laminated body.

[0008] Figure 2 This is a diagram for explaining the substrate after the first step is performed.

[0009] Figure 3 This is a diagram for explaining the substrate after the second step is performed.

[0010] Figure 4 It is a diagram for explaining a method for measuring the resistance value of the laminated body of the Example and the Comparative Example. DETAILED DESCRIPTION

[0011] Hereinafter, the method for producing the laminated body according to the present embodiment will be described in detail.

[0012] The laminate including the substrate and the metal nanowire layer is expected to have low resistance and excellent light transmittance. According to the method for producing a laminate of the present embodiment, a laminate having the above characteristics can be produced.

[0013] In addition, in this specification, "to" is used to mean that the numerical values ​​described before and after it are included as a lower limit and an upper limit.

[0014] The method for producing a laminated body according to the present embodiment includes the following first step and second step. First step: a step of rotating the substrate and spin-coating a composition containing metal nanowires and a solvent (hereinafter also referred to as a "composition") on the surface of the substrate The second step is to rotate the substrate obtained in the first step, and to spin-coat the composition containing metal nanowires and a solvent on the surface of the substrate on which the composition is spin-coated in the first step.

[0015] Hereinafter, the steps of each process will be described using the drawings.

[0016] <First step>

[0017] The first step is a step of rotating the substrate to spin-coat the composition on the surface of the substrate. Figure 1 FIG. 1 is a top view of the substrate 10 used in the first step. Figure 1 As shown, the substrate 10 is in the shape of a perfect circle, and the center of gravity 12 of the substrate 10 is located at the center.

[0018] In the first step, after the composition is supplied to the surface of the substrate 10, the substrate 10 is rotated about the first rotation center 14 (the rotation center of the substrate in the first step). When such a treatment is performed, Figure 2 As shown by the dotted line, the metal nanowires tend to be distributed radially around the position of the first rotation center 14 .

[0019] The following describes in detail the members, materials, and steps used in this process.

[0020] (Base material)

[0021] The substrate is a member used when performing the above-mentioned spin coating, and serves as a member supporting the metal nanowire layer when forming a laminated body described later.

[0022] The substrate is preferably a spectacle lens substrate.

[0023] The type of the spectacle lens substrate is not particularly limited, and examples thereof include common spectacle lens substrates made of plastics, inorganic glass, and the like. From the viewpoint of excellent handleability, a plastic spectacle lens substrate is preferred.

[0024] There is no particular limitation on the type of plastic eyeglass lens substrate, and examples thereof include finished lenses whose convex and concave surfaces are optically finished and molded according to a desired diopter, semi-finished lenses whose convex surfaces alone are finished to be optical surfaces (spherical surfaces, rotationally aspherical surfaces, progressive surfaces, etc.), and lenses whose concave surfaces of semi-finished lenses are processed and ground according to the wearer's prescription.

[0025] The type of plastic (so-called resin) constituting the plastic eyeglass lens substrate is not particularly limited, and examples thereof include (meth)acrylic resins, thiourethane resins, allyl resins, episulfide resins, polycarbonate resins, polyurethane resins, polyester resins, polystyrene resins, polyethersulfone resins, poly-4-methylpentene resins, and diethylene glycol bisallyl carbonate resins (CR-39).

[0026] The thickness of the plastic eyeglass lens substrate is not particularly limited, but is generally about 1 mm to 30 mm in view of workability.

[0027] The refractive index of the plastic eyeglass lens substrate is not particularly limited.

[0028] Furthermore, the plastic eyeglass lens substrate may be opaque as long as it has light transmittance, and may contain an ultraviolet absorber or a dye that absorbs a specific wavelength region from the ultraviolet region to the infrared region.

[0029] The planar shape of the substrate (the shape of the substrate when viewed from the normal direction of the surface of the substrate) is not particularly limited and can be as described above. Figure 1 The shape shown is a perfect circle, but other shapes are also possible.

[0030] (Composition)

[0031] The composition comprises metal nanowires and a solvent.

[0032] From the perspective of lowering the resistance value of the stack (in other words, lowering the resistance value of the metal nanowire layer) (hereinafter also referred to as “lower resistance value”), the metal contained in the metal nanowires contained in the composition is preferably at least one selected from the group consisting of silver, gold, copper, nickel and platinum, more preferably silver or gold, and even more preferably silver.

[0033] In addition, metal nanowires refer to conductive materials that are made of metal, have a needle-like or wire-like shape, and have a nanometer diameter. Metal nanowires can be straight or curved.

[0034] The diameter of the metal nanowires is not particularly limited, but is preferably 500 nm or less, more preferably 200 nm or less, further preferably 100 nm or less, and particularly preferably 40 nm or less in terms of better light transmittance of the metal nanowire layer. The lower limit is usually 10 nm or more.

[0035] The diameter of the metal nanowire is an average value obtained by observing the cross section of the metal nanowire using a scanning electron microscope or a transmission electron microscope, measuring the diameter of the metal nanowire at 20 locations, and taking the arithmetic average of these values. In addition, when the cross section is not a perfect circle, the major axis is used as the diameter.

[0036] The length of the metal nanowire is not particularly limited, but is preferably 5 μm to 1000 μm, more preferably 10 μm to 500 μm, and further preferably 20 μm to 300 μm in terms of lowering the resistance value.

[0037] The length of the metal nanowire is an average value, which is obtained by measuring the lengths of 20 metal nanowires using a scanning electron microscope or a transmission electron microscope and taking the arithmetic average of the lengths.

[0038] The ratio of the diameter d to the length L of the metal nanowire (aspect ratio: L / d) is not particularly limited, but is preferably 10 to 100,000, and more preferably 50 to 100,000.

[0039] The method for measuring the diameter and length of the metal nanowires is as described above.

[0040] The solvent contained in the composition may be water or an organic solvent.

[0041] The type of organic solvent is not particularly limited, and examples thereof include alcohol solvents, ketone solvents, ether solvents, ester solvents, hydrocarbon solvents, halogenated hydrocarbon solvents, amide solvents, sulfone solvents, and sulfoxide solvents.

[0042] Among them, alcohol solvents are preferred, and isopropyl alcohol (IPA) is more preferred.

[0043] The content of the metal nanowires in the composition is not particularly limited, but is preferably 98% by mass or more, and more preferably 99% by mass or more, based on the total solid content in the composition.

[0044] The solid content refers to components other than the solvent in the composition, and even if the components are in a liquid state, they are regarded as solid content.

[0045] The content of the metal nanowires in the composition is preferably 0.1 to 10.0 g / L, more preferably 0.3 to 6.0 g / L, based on the total volume of the composition.

[0046] (Steps of the first process)

[0047] The procedure of the first step is not particularly limited as long as the composition can be spin-coated on the surface of the substrate, and an example thereof includes a method in which the composition is supplied onto the surface of the substrate using a known spin coater and the substrate is rotated.

[0048] The method for supplying the composition on the surface of the substrate is not particularly limited, and known methods can be cited. For example, a method in which a spray nozzle is used to spray the composition to a predetermined position of the substrate can be cited. In addition, the position of the spray composition is preferably the position of the rotation center of the substrate in the first step.

[0049] Furthermore, the composition may be supplied once or in multiple times. When the composition is supplied in multiple times, the substrate may be rotated each time the composition is supplied, or the substrate may be rotated after the composition is supplied multiple times.

[0050] The amount of the composition supplied can be appropriately changed according to the size and type of the substrate used, and the composition. The amount of the composition supplied is preferably 0.1 to 10 mL, more preferably 0.5 to 5 mL.

[0051] The method of rotating the substrate is not particularly limited, and an example thereof is a method using a known spin coater.

[0052] As an example of a method using a spin coater, the substrate can be rotated by holding the substrate on a rotating table in the spin coater and rotating the rotating table.

[0053] Examples of a mechanism for holding the substrate on the turntable include a vacuum suction mechanism for fixing the substrate on the turntable by reducing the pressure using a vacuum pump and a mechanical mechanism for mechanically fixing the substrate on the turntable.

[0054] The rotation speed of the substrate during spin coating is not particularly limited, and may be, for example, 300 rpm to 3000 rpm (rotation per minute), preferably 500 rpm to 2000 rpm.

[0055] After the spin coating composition, a drying treatment to remove the solvent contained in the composition can be performed. As a method for implementing the drying treatment, a heating treatment can be mentioned. The heating temperature during the heating treatment is not particularly limited, but is preferably 70°C to 150°C, and more preferably 90°C to 130°C. As the heating time, it is preferably 0.5 to 90 minutes, and more preferably 1 to 60 minutes.

[0056] <Second step>

[0057] The second step is a step of rotating the substrate obtained in the first step and spin-coating a composition containing metal nanowires and a solvent onto the surface of the substrate on which the composition was spin-coated in the first step. By performing this step, a metal nanowire layer is formed on the substrate.

[0058] In the second step, after the composition is supplied to the surface of the substrate on which the composition is spin-coated in the first step, the substrate 10 is rotated about the second rotation center 16 (the rotation center of the substrate in the second step). The first rotation center 14 and the second rotation center 16 are different in position.

[0059] When such processing is performed, Figure 3As shown by the dotted line, the metal nanowires tend to be distributed radially around the second rotation center 16. Figure 3 As shown, between the first rotation center 14 and the second rotation center 16, there are a plurality of intersection points of the metal nanowires radially arranged around the first rotation center 14 and the metal nanowires radially arranged around the second rotation center 16. In this way, as the number of intersection points of the metal nanowires increases, the resistance value in the in-plane direction can be reduced without reducing the transmittance.

[0060] The materials and steps used in this process are described in detail below.

[0061] The definition and preferred embodiments of the composition used in the second step are the same as those of the composition used in the first step.

[0062] Furthermore, the composition used in the first step and the composition used in the second step may be the same type of composition or different types of composition as long as they contain metal nanowires and a solvent. Different types of compositions refer to, for example, compositions having different concentrations of metal nanowires or compositions using different types of metal nanowires.

[0063] (Steps of the second process)

[0064] The procedure of the second step is not particularly limited as long as the composition can be spin-coated on the surface of the substrate, and examples thereof include a method in which the composition is supplied onto the surface of the substrate and the substrate is rotated.

[0065] As the procedures of the second step, the procedures described in the first step can be mentioned.

[0066] As long as the position of the rotation center of the substrate in the first step is different from the position of the rotation center of the substrate in the second step, the arrangement relationship thereof is not particularly limited.

[0067] More specifically, if Figure 1 As shown, the distance d between the first rotation center 14 and the second rotation center 16 may be greater than 0 mm. From the perspective of lowering the resistance value, the distance d is preferably greater than 3 mm, more preferably greater than 5 mm. In addition, the distance d is not particularly limited, but is preferably less than 30 mm, more preferably less than 20 mm.

[0068] exist Figure 1 In the illustrated embodiment, the first rotation center 14 and the second rotation center 16 are arranged substantially point-symmetrically with respect to the center of gravity 12 of the substrate, but the method for manufacturing the laminated body of the present embodiment is not limited to the above.

[0069] For example, the first rotation center 14 may be located at the same position as the center of gravity 12 of the substrate, and the second rotation center 16 may be located at the same position as the center of gravity 12 of the substrate. In addition, the center of gravity 12 of the substrate may not be located on the line segment connecting the first rotation center 14 and the second rotation center 16.

[0070] <Other Processes>

[0071] The method for producing a laminated body according to the present embodiment may include steps (other steps) other than the first step and the second step described above. The other steps will be described below.

[0072] (Substrate cleaning process)

[0073] The method for producing a laminated body according to the present embodiment may include a substrate cleaning step of cleaning the surface of the substrate before the first step.

[0074] The substrate cleaning step is not particularly limited as long as the surface of the substrate can be cleaned.

[0075] Specific methods for the substrate cleaning step include a method of supplying gas to the surface of the substrate, a method of supplying a cleaning liquid to the surface of the substrate, and a method of bringing a cleaning brush or the like (including cloth, porous body, paper, etc.) containing a cleaning liquid into contact with the surface of the substrate. The substrate cleaning step may be implemented by combining two or more of the above methods.

[0076] (Water supply process)

[0077] In addition, from the perspective of further lowering the resistance value, the method for manufacturing the laminate of the present embodiment may include a water supply step of supplying water to the substrate on which the composition is spin-coated and drying it after spin-coating the composition in the first step and the second step. By performing the above steps, the metal nanowires are further bonded to each other by capillary force.

[0078] As a specific method of the moisture supplying step, there can be mentioned a method of supplying water vapor to the metal nanowire layer until fine droplets (mist) are generated, and drying the metal nanowire layer until the fine droplets disappear.

[0079] The above-mentioned water supplying step may be repeated, and the number of repetitions is preferably 2 to 20 times, and more preferably 3 to 10 times.

[0080] The moisture supplying step is preferably performed after the first step and the second step.

[0081] The above-mentioned water supply process can also be referred to Nano Lett. 2017, 17, 2, 1090-1096 by Y. Liu et al.

[0082] (Third process)

[0083] The method for producing a laminated body of the present embodiment may further include, after the second step, a third step of rotating the substrate obtained in the second step and spin-coating a composition containing metal nanowires and a solvent on the surface of the substrate on which the composition was spin-coated in the second step.

[0084] That is, the manufacturing method of the laminated body of the present embodiment can also have the process of spin coating the composition on the substrate in addition to the above-mentioned first process and second process. The position of the rotation center of the substrate in the third process can be consistent with the position of the rotation center of the substrate in the first process, or it can be different. In addition, the position of the rotation center of the substrate in the third process can be consistent with the position of the rotation center of the substrate in the second process, or it can be different.

[0085] However, the position of the rotation center of the substrate in the third step is preferably different from both the position of the rotation center of the substrate in the first step and the position of the rotation center of the substrate in the second step.

[0086] In addition, the third step may be performed only once or a plurality of times. When the third step is performed a plurality of times, the positions of the rotation center of the substrate in the third steps performed a plurality of times may be identical or different.

[0087] <Laminate>

[0088] The laminate that can be produced by the above-mentioned method for producing a laminate is a laminate including a substrate and a metal nanowire layer.

[0089] Hereinafter, the structure of the manufactured laminated body will be described in detail.

[0090] In addition, since the base material of the laminated body is the same as the base material described above, the description thereof is omitted.

[0091] (Metal Nanowire Layer)

[0092] The metal nanowire layer is a layer formed by performing the first step and the second step. The metal nanowire layer has conductivity and can impart antistatic properties to the substrate.

[0093] The metal nanowire layer is a layer composed of metal nanowires. In other words, the metal nanowire layer is an aggregate of metal nanowires formed by a plurality of metal nanowires being aggregated to form a layer (an aggregate of metal nanowires in a layered form).

[0094] The metal nanowire layer may be arranged so as to cover the entire surface of one main surface of the substrate, or may be arranged so as to cover a portion of one main surface of the substrate. In other words, the metal nanowire layer may be arranged so as to cover at least a portion of the surface of the substrate (particularly one of the two main surfaces of the substrate).

[0095] The coverage of the metal nanowire layer relative to the substrate surface is not particularly limited, but in most cases it is 5.0% or more, preferably 20.0% or more, more preferably 25.0% or more, and further preferably 40.0% or more in terms of better predetermined effects. The upper limit is not particularly limited, and 100% may be cited, and in terms of better transparency of the laminate, it is preferably 85.0% or less, more preferably 75.0% or less, and further preferably 65.0% or less.

[0096] The coverage of the metal nanowire layer is determined by the following method.

[0097] First, the laminate was observed at 500 times magnification using an optical microscope, and three random locations were selected to determine the ratio (%) of the area containing the metal nanowires at each location (500 μm in length, 660 μm in width) to the total area, and the arithmetic average was calculated.

[0098] The average thickness of the metal nanowire layer is not particularly limited, but is preferably 1 nm to 300 nm, more preferably 10 nm to 100 nm, in terms of achieving a more excellent predetermined effect.

[0099] The average thickness of the metal nanowire layer was determined by the following method.

[0100] First, the spectral reflection characteristics of the laminate were measured using an optical measuring device (reflectance measuring machine USPM-RUIII manufactured by Olympus Corporation), and the thickness was determined by a curve fitting method.

[0101] The above-mentioned laminate may include other members besides the substrate and the metal nanowire layer.

[0102] The laminate may include a hard coating layer on the metal nanowires.

[0103] The hard coating layer is a layer that imparts scratch resistance to the substrate and is disposed so as to cover the metal nanowire layer to protect the metal nanowire layer from the outside.

[0104] The hard coat layer is preferably a hard coat layer having a hardness of "H" or higher in pencil hardness based on the test method specified in JIS K5600.

[0105] As the hard coat layer, a known hard coat layer can be used, for example, an organic hard coat layer, an inorganic hard coat layer, and an organic-inorganic hybrid hard coat layer can be mentioned. For example, in the field of eyeglass lenses, an organic-inorganic hybrid hard coat layer is generally used.

[0106] The method for forming the hard coat layer is not particularly limited, and examples thereof include a method of applying a hard coat layer-forming composition on the metal nanowire layer to form a coating film, and subjecting the coating film to a curing treatment such as a light irradiation treatment.

[0107] In addition, the laminate may include a primer layer between the substrate and the metal nanowire layer. The primer layer improves the adhesion of the metal nanowire layer and the hard coating layer to the substrate.

[0108] The material constituting the primer layer is not particularly limited, and known materials can be used, for example, resins are mainly used. The type of resin used is not particularly limited, and examples thereof include polyurethane resins, epoxy resins, phenolic resins, polyimide resins, polyester resins, bismaleimide resins, and polyolefin resins, preferably polyurethane resins.

[0109] The method for forming the primer layer is not particularly limited, and a known method may be used. For example, a method in which a primer layer-forming composition containing a predetermined resin is applied to a spectacle lens substrate and, if necessary, cured to form the primer layer is exemplified.

[0110] In addition, the laminated body may include an antireflection film.

[0111] The structure of the antireflection film is not particularly limited, and may be a single-layer structure or a multi-layer structure.

[0112] As the antireflection film, an inorganic antireflection film is preferable. The inorganic antireflection film refers to an antireflection film composed of an inorganic compound.

[0113] In the case of multilayer structure, preferably alternately stack low refractive index layer and high refractive index layer structure. In addition, as the material constituting the high refractive index layer, for example, the oxide of titanium, zirconium, aluminum, niobium, tantalum or lanthanum can be enumerated. In addition, as the material constituting the low refractive index layer, for example, the oxide of silicon dioxide can be enumerated.

[0114] The method for producing the antireflection film is not particularly limited, and examples thereof include dry methods such as vacuum deposition, sputtering, ion plating, ion beam assisted deposition, and chemical vapor deposition (CVD).

[0115] <Purpose>

[0116] The above-mentioned laminate can be applied to various uses. In particular, when a spectacle lens substrate is used as the substrate, the laminate can be used as a spectacle lens.

[0117] [Example]

[0118] The above-mentioned aspects will be described in more detail below by way of examples and comparative examples, but the present invention is not limited to these examples.

[0119] <Comparative Example 1 and Examples 1 to 3>

[0120] (First process)

[0121] As a substrate, a plano-convex lens substrate (circular, 75 mm in diameter) having a refractive index of 1.60 was prepared. Both surfaces of the plano-convex lens substrate were left untreated.

[0122] First, wipe the surface of the convex side of the plano-convex lens substrate with a non-woven fabric impregnated with acetone to clean the surface. Next, set the plano-convex lens substrate in a spin coater in such a manner that the flat side of the plano-convex lens substrate becomes the vacuum suction cup side. At this time, in Comparative Example 1, the plano-convex lens substrate is set in the spin coater in such a manner that the position of the center of gravity of the plano-convex lens substrate coincides with the position of the rotation center of the spin coater. On the other hand, in Examples 1 to 3, the plano-convex lens substrate is set in the spin coater in such a manner that the distance between the position of the center of gravity of the plano-convex lens substrate and the position of the rotation center of the spin coater becomes half the value of the distance between the rotation centers shown in the table in the latter section. For example, in Example 1, the plano-convex lens substrate is set in the spin coater in such a manner that the distance between the position of the center of gravity of the plano-convex lens substrate and the position of the rotation center of the spin coater is 2.5 mm.

[0123] The position of the rotation center of the spin coater and the position of the rotation center of the substrate in the first step ( Figure 1 The first rotation center 14) shown corresponds to.

[0124] 1 mL of a composition prepared by adding a predetermined amount of isopropyl alcohol (IPA) to a silver nanowire dispersion (EM Japan, NW-AG30-05G-IPA) to adjust the concentration of the silver nanowires to 0.5 g / L was dropped onto the convex surface of the plano-convex lens substrate placed on a spin coater.

[0125] After the above composition was dropped, the plano-convex lens substrate was rotated at 1000 rpm for 60 seconds to spin-coat the above composition (first step).

[0126] In addition, the silver nanowires have a diameter of 30 nm and a length of 30 μm.

[0127] After the spin coating, the plano-convex lens substrate is removed from the vacuum chuck of the spin coater and subjected to the following treatment (corresponding to the above-mentioned moisture supplying step).

[0128] First, exhaled air is blown onto the convex surface of the plano-convex lens substrate for about 1 to 2 seconds, so that mist from moisture contained in the exhaled air is generated on the convex surface. Then, the surface is dried at room temperature for about 5 to 10 seconds until the mist disappears. The above-mentioned treatment of blowing exhaled air and the treatment of drying are repeated 5 times in sequence.

[0129] (Second process)

[0130] Next, the plano-convex lens substrate is set in a spin coater in such a manner that the plane side of the plano-convex lens substrate obtained above becomes the vacuum chuck side. At this time, in Comparative Example 1, the plano-convex lens substrate is set in the spin coater in such a manner that the position of the center of gravity of the plano-convex lens substrate coincides with the position of the rotation center of the spin coater. On the other hand, in Examples 1 to 3, the plano-convex lens substrate is set in the spin coater in such a manner that the position of the rotation center of the spin coater and the position of the rotation center of the substrate in the first step become the value of the distance between the rotation centers shown in the table of the latter section. However, when observed from the upper surface of the plano-convex lens substrate, the position of the rotation center of the substrate in the second step and the position of the rotation center of the substrate in the first step are located at the position sandwiching the center of gravity of the plano-convex lens substrate (refer to Figure 1 ). More specifically, in Example 1, the center of gravity of the plano-convex lens substrate is located at the center of a line segment connecting the position of the rotation center of the substrate in the first step and the position of the rotation center of the substrate in the second step. In addition, the position of the rotation center of the spin coater and the rotation center of the substrate in the second step ( Figure 1 The second rotation center 16) shown corresponds to.

[0131] In addition, in the table, the distance between the rotation centers of 0 mm means that the position of the rotation center of the substrate in the first step coincides with the position of the rotation center of the substrate in the second step.

[0132] 1 mL of the composition used in the first step was dropped onto the convex surface (the surface on which the metal nanowire layer was formed) of the plano-convex lens substrate placed on the spin coater.

[0133] After the above composition was dropped, the plano-convex lens substrate was rotated at 1000 rpm for 60 seconds to spin-coat the above composition to form a metal nanowire layer (silver nanowire layer) (second step).

[0134] After the metal nanowire layer is formed, the plano-convex lens substrate is removed from the vacuum chuck of the spin coater and subjected to a moisture supply treatment in the same manner as in the first step.

[0135] According to the above-mentioned steps, the laminated bodies of Comparative Example 1 and Examples 1 to 3 were obtained.

[0136] <Comparative Example 2 and Examples 4 to 6>

[0137] The silver nanowire dispersion used in the preparation of the above composition was replaced with a silver nanowire dispersion (Ag NW-L30) manufactured by ACS Materials, and the concentration of the silver nanowires in the composition was set to 5.0 g / L. The laminates of Comparative Example 2 and Examples 4 to 6 were obtained in the same order as Comparative Example 1 and Examples 1 to 3. The silver nanowires contained in the composition used to prepare the laminates of Comparative Example 2 and Examples 4 to 6 had a diameter of 30 nm and a length of 150 μm.

[0138] <Comparative Example 3 and Examples 7 to 9>

[0139] The laminates of Comparative Example 3 and Examples 7 to 9 were obtained in the same procedure as that of Comparative Example 2 and Examples 4 to 6, except that the concentration of the silver nanowires in the composition was 0.5 g / L.

[0140] <Evaluation>

[0141] The following evaluations were performed using the laminates obtained in the above Examples and Comparative Examples. The results are summarized in Table 1 described below.

[0142] (Resistance value)

[0143] Regarding the resistance value of the laminated bodies obtained in Examples and Comparative Examples, copper adhesive tapes were attached to the produced laminated bodies, and the resistance value between the copper adhesive tapes was measured as the resistance value of the laminated bodies.

[0144] Reference Figure 4 A method for measuring the resistance value of a laminate will be described.

[0145] First, the copper adhesive tape 22 was cut into pieces with a width of 1 cm and a length of 4 cm, and two pieces of the cut copper adhesive tape 22 were attached to the surface side of the laminate 100 on which the metal nanowire layer was arranged, so that the center of the length direction of the cut copper adhesive tape 22 coincided with the straight line passing through the first rotation center 14, the second rotation center 16, and the center of gravity 12 of the substrate, and the end of the width direction of the cut copper adhesive tape 22 coincided with the end of the laminate 100. The portion of the copper adhesive tape 22 that was not in contact with the laminate 100 was cut out with scissors according to the shape of the end of the laminate 100 to be used as a test object.

[0146] Alligator clips were connected to the copper adhesive tapes of the test object, and a digital multimeter (CDM-16D, manufactured by CUSTOM) was connected to each alligator clip to measure the resistance value. The measured resistance value was defined as the resistance value of the laminate.

[0147] In addition, as the copper adhesive tape, a conductive copper foil adhesive tape (No. 8323, manufactured by Teraoka Manufacturing Co., Ltd.) was used.

[0148] (Transmittance)

[0149] The transmittance of the laminate at a wavelength of 550 nm was measured using Hitachi spectrophotometer U-4100. The transmittance was measured at the center of the laminate.

[0150] In Table 1, the column “AgNW type” indicates the type of silver nanowires contained in the composition, “1” indicates a silver nanowire having a diameter of 30 nm and a length of 30 μm, and “2” indicates a silver nanowire having a diameter of 30 nm and a length of 150 μm.

[0151] In Table 1, the column “Distance between rotation centers” indicates the distance between the position of the rotation center of the substrate in the first step (first rotation center) and the position of the rotation center of the substrate in the second step (second rotation center).

[0152] [Table 1]

[0153] As shown in Table 1, it was confirmed that according to the production method of the present embodiment, a laminated body having a low resistance value and excellent light transmittance can be obtained.

[0154] Description of symbols

[0155] 10. Substrate

[0156] 12 Center of Gravity

[0157] 14 First rotation center

[0158] 16 Second rotation center

[0159] 100 Laminated

[0160] 22 Copper Bonding Tape

Claims

1. A method for producing a laminate comprising a substrate and a metal nanowire layer, The method for manufacturing the laminate comprises the following steps: The first step is to rotate the substrate and spin-coat a composition comprising metal nanowires and a solvent on the surface of the substrate; and In a second step, the substrate obtained in the first step is rotated, and a composition containing metal nanowires and a solvent is spin-coated on the surface of the substrate on which the composition is spin-coated in the first step. The position of the rotation center of the substrate in the first step is different from the position of the rotation center of the substrate in the second step.

2. The method for producing a laminate according to claim 1, wherein: A distance between a position of a rotation center of the substrate in the first step and a position of a rotation center of the substrate in the second step is 3 mm or more.

3. The method for producing a laminate according to claim 1 or 2, wherein: A distance between a position of a rotation center of the substrate in the first step and a position of a rotation center of the substrate in the second step is 20 mm or less.

4. The method for producing a laminate according to any one of claims 1 to 3, wherein: The length of the metal nanowire is 20 μm to 300 μm.

5. The method for producing a laminate according to any one of claims 1 to 4, wherein: The content of the metal nanowires in the composition is 0.3 to 6.0 g / L relative to the total volume of the composition.